1995
DOI: 10.1074/jbc.270.37.21606
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of a Long Form of the β Subunit of the Interferon αβ Receptor That Is Required for Signaling

Abstract: The interferon ␣␤ receptor (IFN␣R) or type I IFN-R is formed by a 110-kDa ␣ subunit or IFNAR and by a ␤ subunit, which has short and long forms (molecular masses of 55 and 95-100 kDa, respectively). In this report, we demonstrate that the IFN␣/␤R cDNA recently cloned corresponds to the 55-kDa or short form of the ␤ subunit, while the 95-100-kDa species reported here corresponds to a longer form of the IFN␣/␤R cDNA that is probably produced by alternative splicing of the same gene. Stable transfection of the ␣ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
172
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(177 citation statements)
references
References 23 publications
3
172
2
Order By: Relevance
“…The IFN-a receptor is present at low numbers on the surface of all cell types and consists of two transmembrane proteins named IFNAR1 and IF-NAR2-2 (Novick et al, 1994;Uze et al, 1990). The IFNAR2 gene generates several alternatively spliced forms, but only the product harboring a long intracytoplasmic domain (IFNAR2-2) is part of a functional IFN-a receptor (Domanski et al, 1995;Lutfalla et al, 1995) (Figure 9). A membrane-proximal 33 amino acid sequence of the cytoplasmic domain of IFNAR1 physically associated with Tyk2 (Colamonici et al, 1994a,b) (Figure 9A).…”
Section: Discussionmentioning
confidence: 99%
“…The IFN-a receptor is present at low numbers on the surface of all cell types and consists of two transmembrane proteins named IFNAR1 and IF-NAR2-2 (Novick et al, 1994;Uze et al, 1990). The IFNAR2 gene generates several alternatively spliced forms, but only the product harboring a long intracytoplasmic domain (IFNAR2-2) is part of a functional IFN-a receptor (Domanski et al, 1995;Lutfalla et al, 1995) (Figure 9). A membrane-proximal 33 amino acid sequence of the cytoplasmic domain of IFNAR1 physically associated with Tyk2 (Colamonici et al, 1994a,b) (Figure 9A).…”
Section: Discussionmentioning
confidence: 99%
“…et al [23] have demonstrated that mutant U1D cells bind IFNc~ with low affinity, and that transfection of Tyk-2 restores high affinity binding. The low affinity binding observed in U 1D cells [23] resembles the low affinity receptors observed in mouse transfectants that only express the human fl subunit of the type I IFN-R [7]. These findings led us to hypothesize that an interaction, either direct or through adapter proteins, between the Tyk-2 and Jak-1 kinases brings together the ~ and fl subunits to form the high affinity receptor.…”
Section: Introductionmentioning
confidence: 84%
“…The role of intermolecular phosphorylation of the homodimer is not clear, but it is possible that it serves as an amplification system which activates neighboring receptors. In a second stage, Tyk-2 and Jak-1 tyrosine phosphorylate the c~ and fl subunit of the receptor, respectively [7,8], and the Statl and Stat2 transcription factors. Our preliminary studies indicate that the Statl and Star2 factors are docked to the flL subunit in a ligand-independent fashion forming a constitutive complex with the receptor and Jak kinases (Domanski et al, manuscript in preparation).…”
Section: Intermolecular Tyrosine Phosphorylation Of the Tyk-2 Dimersmentioning
confidence: 99%
See 1 more Smart Citation
“…The JAKs bind constitutively to receptor subunits, are activated when ligand binding dimerizes the receptor subunits and sequentially phosphorylate multiple components of the signaling cascade. In the case of the type I IFNs, including IFN-a and -b, ligand binding to the IFNaR1 and IFNaR2 receptor subunits juxtaposes and activates Tyk2 and Jak1, the associated JAK kinases (Colamonici et al, 1994;Domanski et al, 1995;Yan et al, 1996b). The JAKs become phosphorylated, and in turn phosphorylate a critical tyrosine on IFNaR1, which functions as a docking site for the Stat2 SH2 domain (Yan et al, 1996a;Li et al, 1997).…”
Section: Introductionmentioning
confidence: 99%